Pelaksanaan Hukum Mati: Kajian Hadis Hukum Riwayat Abdullah Bin Mas'ud - Sulaemang L. (Al-Mizan, 2015)
This paper discusses the legal traditions of the implementation of the death penalty by Abdullah bin Mas'ud narrated. It aims to determine an offense as something forbidden or required by law, if it’s done or omitted, then the person act or neglect will be threatened with punishment. The death penalty is the most severe punishment who handed down to the perpetrators of crimes, because it concerns the human soul. If the penalty is impossed, it ended the convist history. The author uses a sociological, theological and Islamic law approach. The results showed that the murder is one crime that it is very wrath by God Almighty, and it is a major sin. In the language of the Koran, the death penalty is called qişaş, so did the traditions of the Prophet, Which is narrated by Ibn Mas'ud ra. Besides, the problem of killing in the hadith also mentioned the problem of adultery and apostasy, which are both lawful bloods. That is punishable by death. The implications of this study is the death penalty is useful to provide education and teaching, to prevent the spread of crime, ensuring the survival of other human beings, as well as upholding the law of Allah on earth, against the perpetrators, so that people will feel safe from crime criminals.